Antiphospholipid Antibodies From Women With Pregnancy Morbidity and Vascular Thrombosis Induce Endothelial Mitochondrial Dysfunction, mTOR Activation, and Autophagy - Rodríguez, Carlos M.; Velásquez-Berrío, Manuela; Rúa, Carolina; Viana, Marta; Abrahams, Vikki M.; Cadavid, Angela P.; Alvarez, Angela M. (Frontiers in Physiology, 2021)
Antiphospholipid syndrome (APS) is an autoimmune disease characterized by thrombosis and pregnancy morbidity obstetric events together with persistent high titers of circulating antiphospholipid antibodies (aPL). Several mechanisms that explain the development of thrombosis and pregnancy morbidity in APS include the association of aPL with alterations in the coagulation cascade and inflammatory events. Other mechanisms disturbing cellular homeostasis, such as mitochondrial dysfunction, autophagy, and cell proliferation, have been described in other autoimmune diseases. Therefore, the objective of this study was to investigate the impact of aPL from different patient populations on endothelial cell mitochondrial function, activation of the mTOR and autophagy pathways, and cellular growth. Using an in vitro model, human umbilical vein endothelial cells (HUVECs) were treated with polyclonal Immunoglobulin G (IgG) purified from the serum of women with both pregnancy morbidity and vascular thrombosis (PM/VT); with vascular thrombosis only (VT); or with pregnancy morbidity and non-criteria aPL (SN-OAPS). As control groups we included IgG from women with pregnancy morbidity without aPL (PM/aPL-) and healthy women with previous uncomplicated pregnancies (NHS). Mitochondrial function, mTOR activation, autophagy, and cell proliferation were evaluated by Western blotting, flow cytometry and functional assays. IgG from women with PM/VT increased HUVEC mitochondrial hyperpolarization and activation of the mTOR and autophagic pathways, while IgG from patients with VT induced endothelial autophagy and cell proliferation in the absence of elevated mTOR activity or mitochondrial dysfunction. IgG from the SN-OAPS patient group had no effect on any of these HUVEC responses. In conclusion, aPL from women with pregnancy morbidity and vascular events induce cellular stress evidenced by mitochondrial hyperpolarization and increased activation of the mTOR and autophagic pathways which may play a role in the pathogenesis of obstetric APS.